(untitled) - Findlay, Alexander (New York, 1960)
Purchase of this book includes free trial access to www.million-books.com where you can read more than a million books for free. This is an OCR edition with typos. Excerpt from book: CHAPTER III THE CHEMISTRY OF ILLUMINANTS At the present time when, by the mere touch of the finger on a button, we can instantly obtain a flood of brilliant light, it is difficult to realise what must have been the conditions of life when man had to be content with the smoky flame of the pine torch or of the rush dipped in olive oil which burned with but a feeble light even in its vase of finest workmanship. Think also of the old guttering candle, with its constant need of "snuffing," and you will understand how great has been the advance in the direction of artificial illumination; and practically the whole of this advance has taken place since the beginning of the nineteenth century.
Keywords: Chemistry, technical